Revision of the family Carabodidae (Acari: Oribatida) XVII. Redescription of Diplobodes africanus Mahunka, 1987 from Kenia. Description of Diplobodes thailande sp. nov. from Thailand and Rwandabodes kayoveae gen. nov., sp. nov. from Rwanda - Fernandez, Nestor; Theron, Pieter; Leiva, Sergio; Jordaan, Anine (Zootaxa, 2019)
Diplobodes africanus Mahunka, 1987, is redescribed by using Scanning Electron Microscopy (SEM) in order to complement optical microscopy. Diplobodes thailande sp. nov. from Thailand is described. For both species we include inclined views, to permit detailed analysis of ventral regions and to aid understanding of the complex relationships between elevated and depressed zones. Diplobodes thailande sp. nov. presents previously undescribed structures on legs III, which are involved in the leg folding process. Rwandabodes kayoveae gen. nov., sp. nov. presents a series of particular characteristics, such as: elevated interlamellar process on prodorsum, composed of a triangular structure, externally delimited by a low lamellar furrow; in setae inserted on elevated interlamellar process; large free lamellar tip; notogaster lacking ridges; anterior genital furrow extends into an oblique lateral depression; depressed area anterior to anal zone; both zones clearly delimited. These characteristics permit easy differentiation from related genera.